Development of students' creative abilities using аrt technologies (using the example of quilling and ebru methods) (Journal of Educational Sciences, 2021)
The development of students’ creative abilities is analyzed in the article. Art technologies are offered to train future creators and competitive specialists who are able to make decisions in complex non-standard situations. The concepts of “creativity” and “creative abilities” in the conceptual apparatus of the study are compared. The conditions and the proposed principles are considered, with the help of which it is possible to organize the educational process for the continuous development of students’ creative abilities. The content of the quilling technique, the Ebru technique aimed at the development of creativity among students are presented in the article. The use of art technologies helps to relieve tension, emotional stress of a person. The effective use of art technologies helps to stabilize the psychological microclimate in the academic building and in the classroom. Art-technology is the teaching of intellectual activity through artistic creativity. Art technologies allow students to express themselves, as well as in the form of psychological assistance to clients, they can increase the self-esteem of a person who is capable of self-regulation and self-control. The results of an experimental work in which 100 people took part are presented in the practical part of the research. The research was conducted on the basis of the Al-Farabi Kazakh National University. On the basis of the created methodology mediated by the techniques of quilling and Ebru, students’ self-esteem was normalized, emotional stability and creative abilities were developed Key words: creative activity, independent work, exploratory activity, student, art technology, educational process, the ability.